Protection of Human Rights: Efforts to Solve The Crime of Genocide in the Muslim Community - Bagus Rahul Ahmad Attaufa (Yayasan Mentari Madani, 2023)
he crime of genocide has long been a serious threat to Muslim communities around the world. In this article, the protection of human rights has taken center stage. This article aims to investigate the efforts that have been made to overcome the crime of genocide that threatens Muslim communities. We explore the background to these crimes, explore recent developments in human rights protection, and analyze the various solutions and initiatives that have been implemented by international organizations, governments, and civil society groups. We use a qualitative approach based on normative juridical research methods, namely research conducted based on primary legal material by examining theories, concepts, legal principles and statutory regulations related to this research. We also identify factors that trigger the crime of genocide. Conflict resolution can be resolved in court and outside court. If a case is resolved outside of court, it can be done by mediation and negotiation, but if it is done in court, which in this case applies to an international court, then the settlement can be resolved by the International Criminal Court